Utilization of E-commerce and Social Media to Support Sustainable Business: Systematic Literature Review - Triono, Edy; Nurjayanti, Atri Yunita; Prasetyowati, Andy; Wardana, Ludi Wishnu; Murwani, Fulgentius Danardana (PT. EQUATOR SINAR AKADEMIA, 2024)
The digitalization transformation has brought significant changes to the business world. In this context, e-commerce and social media have become two important aspects that influence business development. This research aims to analyze the impact of business digitalization transformation, especially in terms of the use of e-commerce and social media to support sustainable business. This study uses a systematic literature review (SLR), namely the library research method sourced from Scopus and Emerald Publishing databases. The results of this literature review research can be used to broaden insight and knowledge regarding the features of e-commerce and social media in supporting sustainable business, as well as being a consideration for business actors in making decisions to develop sustainable business.